Upaya Meningkatkan Hasil Belajar IPA dengan Materi Pokok Keanekaragaman Hayati melalui Penerapan Metode Berbasis Inquiri - Kustiyati, Retno (Journal of Education Action Reseach, 2018)
Based on observations made by researchers on learning activities and interviews with teachers obtained data, that the learning outcomes of science subjects with biodiversity material for class X students of State Vocational High School 60 Jakarta for 2014/23015 school year, are still under KKM and still need improvement - improvement in the learning process because the pre-cycle test results showed values with an average of 68.96 and learning completeness reached 57.57%. To overcome these problems the researchers sought to make improvements through the implementation of inquiry-based learning on IP subjects with biodiversity material for students in class X of the first semester of SMK Negeri 60 Jakarta. This research was conducted at SMK Negeri 60 Jakarta in 2014/2015 academic year with a total of 32 students. This research was conducted in two cycles. The indicator of the success of this research is that during the learning process and reflection it is evident that there is an increase in learning outcomes in science subjects in class X of the First Semester of SMK Negeri 60 Jakarta. The results of his research are: learning outcomes in the first cycle the average value shows 75.51, while the learning outcomes in the second cycle the average value shows. 79.30. Based on research data and discussion, it can be concluded that applying learning through inquiry-based methods in science subjects can improve student learning outcomes in class X of the first semester of SMK Negeri 60 Jakarta.